Electrophysiological Evaluation of Carpal Tunnel Syndrome in Patients with post-COVID Neuropathy (Bangladesh Journal of Neuroscience, 2026)
Background: The COVID-19 pandemic is caused by severe acute respiratory syndrome caused by coronavirus 2 (SARS-COV-2). Although the predominant clinical presentation is respiratory disease, neurological manifestations are increasingly recognised. The study aimed to evaluate the frequency of carpal tunnel syndrome among COVID-19 neuropathy patients and establish a causal link between carpal tunnel syndrome and COVID-19 infection. Electrophysiological evaluation of carpal tunnel syndrome can be used as a diagnostic as well as a prognostic marker so that patients can undergo an early therapeutic trial.Objective: The objective of this study was to see the frequency and electrophysiological pattern of post-COVID carpal tunnel syndrome.Methods: This cross-sectional observational study was undertaken in the Department of Neurology, BSMMU, Dhaka, Bangladesh. Non-randomized convenient purposive sampling was done to selected COVID neuropathy patients. A total of 44 patients were selected purposively. Study subjects were taken from confirmed cases of COVID-19 infection with symptoms of neuropathy admitted at the COVID unit and visited at COVID follow-up Clinic of BSMMU, Dhaka, after meeting inclusion and exclusion criteria from October 2020 to March 2022. Detailed history, physical examination findings, previous medical records, and investigation findings were recorded in the data ‘sheet. An electrophysiological evaluation of neuropathy was done for each patient.Results: Out of 44 patients, most of the pathological forms of neuropathy were demyelinating (44.4%), followed by axonal (40.7%), and the rest were mixed (14.8%). We found polyneuropathy 14 (51.9%), carpal tunnel syndrome 7(25.9%), and 3(11.1%) mononeuropathy. Among 7 Carpal Tunnel Syndrome patients, we found four patients had unilateral (two right and two left), and three had bilateral involvement.Conclusion: Electrophysiologically we found various types of neuropathies among our patients. Carpal tunnel syndromes and related neuropathies appear to be possible sequelae of COVID-19 infection. So electrophysiological examination could be done for patients with symptomatic carpal tunnel syndrome after Covid 19 infection.